The Roles of The Office of Public Works and Spatial Planning (PUPR) in Flood Prevention Program in Bengkulu City, Bengkulu Province (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
Bengkulu City is situated in a geographical location that makes it susceptible to various natural disasters caused by climate, weather, and other natural factors. Human activities, such as the mismanagement of drainage systems, contribute to the occurrence of floods in the city. The responsibility for addressing these floods falls upon the Public Works and Spatial Planning Service (PUPR), which is tasked with providing basic services and managing regional government affairs in accordance with Law Number 23 of 2014 concerning Regional Government. While PUPR has achieved a percentage of its drainage maintenance targets in 2020, flooding continues to affect certain areas of Bengkulu City. Hence, this study aims to investigate the role of PUPR Service in preventing recurrent flooding in the city. A descriptive qualitative design with an inductive approach was employed for the research, utilizing interviews, observation, and documentation as data collection techniques. The selection of informants was based on purposive and snowball sampling techniques. Data analysis involved data reduction, presentation, and drawing conclusions through data triangulation to ensure validity. The study findings reveal that PUPR Service's role in flood prevention is guided by the Bengkulu Mayor Regulation Number 56 of 2016, which outlines the functions and responsibilities of Bengkulu City Regional Offices. While the results have been somewhat satisfactory, they are not yet optimal due to several obstacles in the field. These challenges include a shortage of skilled personnel, damaged equipment, budget deficits, a lack of a comprehensive drainage development plan, waste management issues, and uncontrolled urbanization.ABSTRAK Kondisi geografis yang dimiliki Kota Bengkulu menjadikannya sebagai salah satu daerah rawan bencana alam yang diakibatkan oleh iklim, cuaca atau faktor alamiah. Bencana alam yang terjadi juga disebabkan oleh faktor non alamiah yang dilakukan oleh manusia, sebagai contoh adalah banjir. Banjir di kota Bengkulu ditangani oleh Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) sebagai salah satu pelaksana pelayanan dasar dan penyelenggara urusan pemerintahan daerah Kabupaten/Kota sebagaimana amanah Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Pada tahun 2020, capaian persentase realisasi penanganan drainase kondisi baik, rasionya melebihi dari persentase target capaian. Namun, banjir masih saja terjadi pada beberapa titik lokasi di Kota Bengkulu. Penelitian ini bertujuan untuk mengetahui peranan Dinas PUPR dalam mencegah terjadinya banjir berulang di Kota Bengkulu. Metode penelitian yang digunakan adalah desain kualitatif deskriptif dengan pendekatan induktif. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Infoman ditentukan dengan teknik purposive and snowball sampling. Analisis data dilakukan dengan cara reduksi data, penyajian data dan penarikan kesimpulan dengan menguji keabsahan data menggunakan triangulasi data. Hasil penelitian menunjukkan bahwa Peranan Dinas PUPR dalam mencegah terjadinya banjir berpedoman pada peraturan tertulis yang tertera dalam Peraturan Walikota Bengkulu Nomor 56 Tahun 2016 tentang Uraian dan Fungsi Dinas Daerah Kota Bengkulu dengan hasil sudah berjalan cukup baik namun belum optimal. Hal tersebut disebabkan oleh masih adanya beberapa kendala dilapangan seperti kurangnya kualitas dan kuantitas SDM pelaksana teknis operasional, rusaknya alat berat yang dimiliki, defisit anggaran, belum adanya masterplan pembangunan drainase, masalah pengelolaan limbah sampah serta pembangunan yang tidak terencana.